2018
DOI: 10.1111/resp.13387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of emphysema on physiological and prognostic characteristics of lung function in idiopathic pulmonary fibrosis

Abstract: In IPF, emphysema to an extent of ≥10% affects both the annual decline rate and the prognostic significance of FVC. This extent could be used to define CPFE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 34 publications
0
36
0
1
Order By: Relevance
“…As lung function progression might be affected by smoking status besides pulmonary fibrosis, 19 , 20 the mean change of FVC% pred and DLco% pred between smokers and non-smokers in patients who received pirfenidone treatment was compared. Although no statistical difference was found between different smoking status, non-smokers had the tendency to benefit more from pirfenidone treatment, reflected by the reduction in their lung function decline.…”
Section: Discussionmentioning
confidence: 99%
“…As lung function progression might be affected by smoking status besides pulmonary fibrosis, 19 , 20 the mean change of FVC% pred and DLco% pred between smokers and non-smokers in patients who received pirfenidone treatment was compared. Although no statistical difference was found between different smoking status, non-smokers had the tendency to benefit more from pirfenidone treatment, reflected by the reduction in their lung function decline.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al [15] reported that IPF was concomitant with emphysema in some lung fields in 42% of their patients, and this finding was based on high-resolution CT. In the present study, patients with CPFE had an LAA score ≥7, which implied that the lung field with emphysema was larger and the lung field with fibrosis was smaller in the CPFE group than the lung field with emphysema and the lung field with fibrosis in the IPF group.…”
Section: Discussionmentioning
confidence: 92%
“…Yoon et al [15] reported that IPF developed concomitantly with emphysema in some lung fields in 42% of their patients, and this finding was based on high-resolution CT. In the present study, patients with CPFE had an LAA score ≥7, which implied that the lung field with emphysema was larger and that with fibrosis was smaller in the CPFE group, than the lung field with emphysema and the lung field with fibrosis in the IPF group.…”
Section: Discussionmentioning
confidence: 94%